1975
DOI: 10.1016/s0022-5347(17)59448-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Urinary Polyamines in the Diagnosis of Genitourinary Tract Malignancy

Abstract: Normal ranges for urinary polyamines have been obtained. Non-malignant genitourinary tract disease is not associated with elevated urinary polyamines. A high correlation exists between the presence of active urologic cancer and elevated urinary excretion of polyamines. Post-treatment polyamines correlate with the continued presence or absence of genitourinary tract malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As early as the mid-1970s, Sanford et al discovered that the excretion of polyamines in the urine of patients harboring PCa was higher than normal individuals [ 56 ]. In the same year, Fair et al reported a significant elevation of urinary spermidine content by Spectronic 20 colorimeter in PCa patients, but not putrescine and spermine [ 57 ].…”
Section: Spermine As a Biomarker For Pcamentioning
confidence: 99%
“…As early as the mid-1970s, Sanford et al discovered that the excretion of polyamines in the urine of patients harboring PCa was higher than normal individuals [ 56 ]. In the same year, Fair et al reported a significant elevation of urinary spermidine content by Spectronic 20 colorimeter in PCa patients, but not putrescine and spermine [ 57 ].…”
Section: Spermine As a Biomarker For Pcamentioning
confidence: 99%
“…Studies on elevated urinary polyamine levels have been reported in prostate carcinoma [4,6] and have been claimed as a valuable tool for the diagnosis of prostatic cancer. These findings suggest an altered polyamine pro file in the tissues.…”
Section: Discussionmentioning
confidence: 99%